Adjusting to and thriving in a new school: Role of students’ expectations, educational attitudes, and resilience during secondary school transition - Kwarikunda, Diana; Gladys, Nakalema; Muwonge, Charles Magoba; Ssenyonga, Joseph; Schiefele, Ulrich (International Journal of School & Educational Psychology, 2023)
For some students, the transition from primary to secondary school is a difficult and stressful event that can have potential negative effects on their psychological wellbeing, social adaptability, and academic achievement. Although several individual, environmental, and family protective factors have been investigated, direct and indirect contributions of expectations and educational attitudes on resilience have not yet been fully explored. In the present study, using a sample of 744 (8 schools, Study 1) and 39 (3 schools, Study 2) 8th grade (day or boarding) secondary school students in Uganda, we initially explored: (1) gender and residence status differences in transitioning students’ resilience and educational attitudes, (2) predictive effects of educational attitudes, gender and residence status on resilience, (3) the direct and indirect effects of educational attitudes and expectations on resilience, and (4) the students’ perspectives about the transition process. In study 1, data were collected using self-report questionnaires whilst in study 2 data were collected from focus group discussions. Quantitative results indicate that (i) girls reported to have received more physical care for better adjustment than boys, whilst day and male students reported to have received more psychological care during school adjustment than their counterparts, (ii), residence status was a stronger predictor of resilience than were gender and educational attitudes, and (iii) student’s expectations had direct and indirect effects on resilience through educational attitudes. Results of the thematic analyses show that transitioning students have unrealistic expectations and mixed feelings during adjustment. To foster resilience of transitioning students, schools could cultivate a culture of high realistic expectations, peer connectedness, and positive educational attitudes, as well as organize several transitional strategies and activities that involve parents throughout the first year of lower secondary school.
Keywords: Resilience; School transition; Educational attitudes; Mixed methods research